PENGARUH FAKTOR MIKROEKONOMI DAN MAKROEKONOMI TERHADAP KEBIJAKAN HUTANG PERUSAHAAN - Tika Larasati Harjito Putri; Ratna Septiyanti; Widya Rizki Eka Putri (Jurnal Akuntansi dan Keuangan (JAK), 2019)
The purpose of research is to get empirical evidence about the effect of microeconomics and macroeconomics factors to debt policy. This research used the Financial Companies which is listed in Indonesia stock exchange started the year 2014-2018 with total 32 Companies. Samples are selected based on purposive sampling method with the purpose to get sample according to research aim. Sample consists of 160 observations. The analytical technique was multiple regressions. The research results show that microeconomics factors which are proxied by corporate growth, corporate size, and blockholder ownership has significant effect to debt policy. However, macroeconomics factors which are proxied by political stability and inflation rates has no significant effect to debt policy.